Religious Feeling : Worship Practice Experience for Children Aged 5-6 - Titik Nurhidayatul Fitri; Yuli Kurniawati Sugiyo Pranoto (STAI Hubbulwathan Duri, 2023)
Children's worship practices organized at school and at home should be based on the awareness of religious feelings. The importance of children's awareness of religious feeling is the main reason for success in children's religious and spiritual development. This study aims to analyze children's worship practice preferences and the emotional expressions shown towards these preferences. This research is a descriptive qualitative research. The number of respondents was 32 children with different school backgrounds, namely, Public kindergarten, Privat Kindergarten and Islamic Privat Kindergarten. Data collection was done with picture-based interviews (worship practices, worship partners and emotional expressions). As a result, most children chose prayer and read Quran as their preferred worship practices. The most chosen worship partner is a friend. The majority of children received motivation to worship from their peers. The enthusiasm for intensive worship is shown during the month of Ramadan, where children together with their friends worship at the mosque. Religious feelings is formed from children's worship habits such as prayer, read Quran, fasting and alms. The most chosen expression of emotion is very happy with the majority reasons are being happy to worship with friends.